Meibomian gland carcinoma of the lower eyelid: a rare case - Behera, Madhusmita; Dhar, Subhra (International Journal of Research in Medical Sciences, 2020)
Meibomian gland carcinoma (MGC) is a rare but highly malignant slow growing tumor of the eyelid. MGC usually arises from meibomian gland located in the tarsal plate although rarely it can originates in the gland of zeis, sebaceous gland of caruncle, and periocular skin. MGC is more common in cases of elderly females. Upper eyelid is more commonly affected where the meibomian glands are more. Early diagnosis is very important but in most of the cases the diagnosis is delayed as it mimics chalazion or blepharo-conjunctivitis. This leads to inappropriate treatment and increase in morbidity and/or mortality. Special feature of this carcinoma is that it spread intra-epithelial and causes skipped lesions.